2016
DOI: 10.1021/acs.est.5b04252
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes of PBDE Levels in California House Cats and a Link to Cat Hyperthyroidism

Abstract: In this study, we measured serum PBDE levels in California (CA) house cats during two time periods: 2008-2010 and 2012-2013 to assess the impacts of the decline in use of these materials after the bans. The median ∑19PBDE level in CA household cats (age ≥10 yr) was 3479 ng/g lipid in 2008-2010 (1st time period, n = 21) and 1518 ng/g lipid in 2012-2013 (2nd time period, n = 22), about 2 times lower than in the first time period (p = 0.006). In contrast, PCB and OCP levels showed no statistically significant cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…It has been reported that in certain areas (especially urban areas) of developing countries, exposure to PCBs is high due to the exposure to WEEE (11). Also in previous studies in cats from France (13) or USA (19), the cats also exhibited higher serum levels of PCBs, and also a higher variety of congeners detected. However, it has been reported that a geographical gradient in the level of PCB contamination exists, and the pattern varies greatly from region to region (30).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…It has been reported that in certain areas (especially urban areas) of developing countries, exposure to PCBs is high due to the exposure to WEEE (11). Also in previous studies in cats from France (13) or USA (19), the cats also exhibited higher serum levels of PCBs, and also a higher variety of congeners detected. However, it has been reported that a geographical gradient in the level of PCB contamination exists, and the pattern varies greatly from region to region (30).…”
Section: Discussionsupporting
confidence: 52%
“…Currently, the only compound of the BDE family that is still approved for use is BDE-209 (), and it has to be taken into account that unfortunately this chemical was not included in this study, because it can not be determined in our laboratory due to technical limitations. In any case, and even without having included the BDE 209, our results are very similar to those reported in cats from Pakistan (median ∑BDEs = 6.1 ng/g fat) (29), USA—Georgia, Massachusetts, and North Carolina—(median ∑BDEs = 5.9 ng/g fat) (17), but lower than those reported in Sweden (median ∑BDEs = 24.1 ng/g fat) (34), and than in those cats from California, in which the authors reported extraordinarily high levels of BDEs (median ∑BDEs = 2904 ng/g fat), mainly due to the high levels of BDE-99 detected in those animals (19). While diet, mainly through fish intake, is considered the main route of exposure for PCBs (23, 3537), the ingestion of dust from the environment is considered the most important route of exposure for BDEs in cats (38).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Of six small cross-sectional studies of PBDEs and feline hyperthyroidism, two reported associations between PBDE concentrations in blood (on a lipid weight basis) and hyperthyroidism. 51,5458 However, feline hyperthyroidism causes substantial weight loss. As PBDEs are lipophilic, weight loss will tend to increase concentrations of such compounds in body lipids, including blood lipid.…”
Section: Reverse Causationmentioning
confidence: 99%
“…Thus the reported associations may be at least partly due to reverse causation (Figure 5). 54 Use of dust as a proxy exposure measure has the potential of mitigating the reverse causation because if reverse causation accounts for the association between blood PBDE and feline hyperthyroidism, then no association between dust concentrations and hyperthyroidism would be seen (Figure 5). …”
Section: Reverse Causationmentioning
confidence: 99%